2014
DOI: 10.1161/circresaha.114.302761
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive (T and B Cells) Immunity and Control by Dendritic Cells in Atherosclerosis

Abstract: 14 Altogether, these early observations on the presence of T cells in human and in mouse atherosclerotic plaques remained associative and did not show causation.Subsequent studies using animal models of atherosclerosis, especially Apoe -/-or Ldlr -/-mice, in which human-like atherosclerotic lesions develop spontaneously or in response to high-fat diet, provided more direct evidence for the participation of adaptive immunity in atherogenesis. Apoe -/-or Ldlr -/-mice crossed with immunodeficient mice that lack t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 302 publications
(315 reference statements)
2
128
1
Order By: Relevance
“…Meanwhile, in case of HDL cholesterol, it could affect atherosclerosis which has been identified as an inflammatory process 40) driven by the adaptive (T and B cells) immune system and dendritic cells. 41) In our study, a rise of HDL cholesterol might be favorably associated with early inflammatory process for establishment of good coronary flow in STEMI patients. In addition, this study showed that the final coronary flow after PCI was better in LCX territory than in other treated arteries in NSTEMI (HR 0.544 [0.304-0.975], P = 0.001), even after the adjustment for the presence of other factors.…”
Section: Discussionmentioning
confidence: 50%
“…Meanwhile, in case of HDL cholesterol, it could affect atherosclerosis which has been identified as an inflammatory process 40) driven by the adaptive (T and B cells) immune system and dendritic cells. 41) In our study, a rise of HDL cholesterol might be favorably associated with early inflammatory process for establishment of good coronary flow in STEMI patients. In addition, this study showed that the final coronary flow after PCI was better in LCX territory than in other treated arteries in NSTEMI (HR 0.544 [0.304-0.975], P = 0.001), even after the adjustment for the presence of other factors.…”
Section: Discussionmentioning
confidence: 50%
“…7) The high degree of maturity of dendritic cells helps T cells differentiate toward the T-helper 1 lineage, and down-regulates the number of circulatory Tregs. 32) In addition, the differentiation of Tregs is influenced by cytokines including IL-10 and TGF-β 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic lesions are characterized by progressive accumulation of lipids, macrophages, NK cells, T and B lymphocytes, smooth muscle cells, and fibroproliferative elements in the intima of arteries [12,13] . Functional analysis of different T-cell subsets role identified the T H 1 responses as proatherogenic, whereas T H 2 immune responses exert antiatherogenic actions [14,15] . Atherosclerosis is also associated with B-cell activation, and traditional T cell-driven B2 cells responses promote atherosclerosis, while innate B1 cells provide protective action through the secretion of naturally occurring antibodies [14,15] .…”
Section: Atherosclerosismentioning
confidence: 99%
“…Functional analysis of different T-cell subsets role identified the T H 1 responses as proatherogenic, whereas T H 2 immune responses exert antiatherogenic actions [14,15] . Atherosclerosis is also associated with B-cell activation, and traditional T cell-driven B2 cells responses promote atherosclerosis, while innate B1 cells provide protective action through the secretion of naturally occurring antibodies [14,15] . Several authors have hypothesized that the number of different pathogens, including T. gondii [16] , may promote synergistic inflammatory responses that are capable of triggering and exacerbating atherosclerosis [17] .…”
Section: Atherosclerosismentioning
confidence: 99%